Pet Health Management System for Gebuu Veterinary Clinic - Ahmad, Miza Syahira; Salamat, Mohamad Aizi (Applied Information Technology And Computer Science, 2023)
Pet Health Management System for GeBuu Veterinary Clinic is a way to help the pet owner set an appointment by using web bases system and not the old way by call the clinic to make appointment and fill in a form using pen each time visit the clinic. It is to ease the owner in applying appointment to check on their pet health. Owner can also check their pet vaccination or health history at the website, by choose which pet that he/she want to see if there multiple pets. With this system the owner does not need to search their pet card each time. While the admin that is the staff will manage the schedule of the appointment, make an order for medicine and reply to the question that will be ask and the vet can see the schedule and update the treatment that has been perform through the pet. While the supplier can also access the system but they can see the application order, update on the status application, delivery data and order history.